إخطار المحكمة الدستورية في ظل التعديل الدستوري 2020 - - أحمد رزق. - عبد الغني بن عمير. (جامعة المسيلة, 2022)
إن ممارسة المحكمة الدستورية لوظائفها، لا سيما الوظيفة الرقابية تتوقف على آلية الإخطار حيث منح المؤسس الدستوري الجزائري في التعديل الدستوري سنة 2020 سلطة إخطار المحكمة الدستورية العديد من الجهات والتي عانتها المادة 193 من التعديل، إذ يشمل الأخطار جميع النصوص التشريعية والتنظيمية والمعاهدات والأوامر التي يصدرها رئيس الجمهورية، ويكون إما إخطار وجويي او إخطار جوازي وذلك حسب نوع الرقابية المفروضة على النص حيث تنوع الرقابية بين رقابة المطابقة ورقابة الدستورية ورقابة توافق القوانين والتنظيمات مع المعاهدات، هذا من جهة، ومن جهة ثانية رقابة فيلية وجويرية وأخرى جوازية، ورقابة بعدية جوازية. الكلمات المفتاحية: ألية الإخطار، الدفع بعدم الدستورية، المحكمة الدستورية، التعديل الدستوري. Abstract: The Constitutional Cout's exercise of its functions, especially the as the Algerian supervisory function, depends on the notification mechanism constitutional founder granted in the constitutional amendment in 2020 the power to notify the Constitutional Court to several bodies that were defined by Article 193 of the amendment, as notification includes all legislative and regulatory texts, treaties and orders issued by the President The republic, and it is either a mandatory notification or a mandatory notification, depending on the type of control imposed on the text, as the censorship varies between compliance control, constitutional control, and the compliance of laws and repulations with treaties, on the one hand, and on the other hand, trbal and mandatory and other permissible control, and passive postal control. Keywords: Notification Mechanism Pleading for Unconstitutionality, Constitutional Cout, Constitutional Amendment.
Keywords: ألية الإخطار، الدفع بعدم الدستورية، المحكمة الدستورية، التعديل الدستوري.